COMMUNITY SERVICE OF MOTHER'S EDUCATION IN THE CREATIVITY OF MP-ASI BASED ON LOCAL FOOD INGREDIENTS FISH AND MORINGA LEAVES AS A SELF-CARE EFFORT TO PREVENT STUNTING IN THE SUB-DISTRICT THE FIELD - Nurliaty; Yani Lestari; Roy Wilson Sihaloho (Cattleya Darmaya Fortuna, 2024)
Stunting is a chronic nutritional problem that inhibits the physical and cognitive growth of toddlers due to long-term malnutrition. This community service activity (PkM) aims to improve the knowledge, attitudes, and practical skills of mothers regarding self-care behavior in fulfilling the nutrition of toddlers through the manufacture of creative Complementary Foods (MP-ASI) based on local foods with high nutritional value, namely fish and moringa leaves (Moringa oleifera). The activity was carried out in Medan Tuntungan District by the academic team from STIKes Darmo Medan. The intervention involved persuasive public health counseling on the importance of micronutrients and demonstration of psychomotor skills in processing local food into a varied MP-ASI menu. Program evaluations are designed using a comparison of pre-test and post-test results to measure participants' levels of understanding and skills before and after the intervention. The results of the activity showed an increase in the enthusiasm and understanding of mothers under five in cutting the chain of stunting from the smallest family unit. In conclusion, structured education on the optimization of MP-ASI based on local commodities that is economically effective in stimulating creativity and building family food independence to support optimal child growth and development.